ECONOMIC RISE OF CHINA AND GEOECONOMICS OF SOUTH CHINA SEA - Tatheer Zahra Sherazi; Fouzia Amin; Bakare Najimudeen (ASIAN Journal of International Peace & Security (AJIPS), 2021)
China is the second largest economy of the world in terms of Gross Domestic Product (GDP) while the largest economy in terms of purchasing power parity (PPP). China is the largest manufacturing economy as well as the largest exporter of goods. Much of China’s trade goes through sea routs; approximately 80 percent of its trade predominantly the energy resources pass through South China Sea. For its geostrategic location and abundance of resources South China Sea holds central position in foreign as well as internal affairs of China. The Theory of Geoeconomics is applied to understand China’s tremendous growth at multiple fronts and the threshold of the growth predicted for setting up a stage to change the global power hierarchy. It has been analyzed that China’s claims on vast portion of the South China Sea, either legal, illegal or historical are closely connected with its economic development and prosperity in broader context of geo-economics. This study employs descriptive, qualitative and analytical approach to explain the dynamics of South China Sea along with development of China grabbing much global attention.